Confirmation of the occurrence of the sandbar shark Carcharhinus plumbeus (Nardo, 1827) at Norfolk Island, Tasman Sea - Duffy, C.a.j.; Scott, M. (Zootaxa, 2016)
The occurrence of the sandbar shark Carcharhinus plumbeus at Norfolk Island is confirmed. Carcharhinus plumbeus occurs over the mid to outer insular shelf from 38 m to at least 53 m depth, and appears to be at least as abundant as C. galapagensis in this habitat. No C. plumbeus were caught from shore despite most fishing effort being land-based. The presence of young-of-the-year confirms C. plumbeus breeds on the Norfolk Island shelf. Size at birth and the timing of parturition appear similar to that reported for eastern Australia.